MOF-derived Co catalysts modified with RuO2 for durable Li-O2 batteries - Yajun Zhao; Guocai Zheng; Guofei Li; Hanqing Liu; Xiaojing Li (Scientific Reports)
Abstract Li-O2 batteries have attracted increasing attention due to their high theoretical specific capacity. However, their practical application is limited by factors such as excessively high overpotential and poor rate and cycle performance. It is crucial to find high-efficiency catalysts to improve the kinetics of the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), as well as to provide sufficient space to store undecomposed Li2O2. In this report, we use a simple hydrothermal synthesis method to compound RuO2 particles on the surface of Co3O4 using the ZIF-8@ZIF-67 double metal-organic frameworks (MOFs) structure as a template. The Co3O4/RuO2 material exhibits excellent bifunctional catalytic performance for both ORR and OER, with improved onset potential and half-wave potential comparable to commercial Pt/C. Meanwhile, the Li-O2 battery demonstrates a high specific capacity of 11,304 mA h g− 1, excellent rate performance, and outstanding cycle stability.